THE IMPORTANCE OF EFFECTIVE IMPLEMENTATION OF FOREIGN INNOVATIVE TECHNOLOGIES IN THE TEACHING OF FOREIGN LANGUAGE COMPETENCIES - Yuldasheva F.; Rashidova Sora (Journal of new century innovations, 2023)
Annotation: The significance of modern teaching technologies in the learning process, principally the use of interactive teaching methods,pedagogical technologies in teaching foreign languages and the utilization of innovative educational technologies is highlighted in this article.